Mental preparation in runners: gender differences, competition levels, and psychological training effects on performance - Kelemen, B.; Tóth, R.; Benczenleitner, O.; Tóth, L. (Frontiers in Sports and Active Living, 2024)
Introduction: The present study aimed to investigate the mental and sports psychological preparation, as well as tactical preparation, of distance runners for competition. We examined whether there are differences based on gender, competition level and various race disciplines, as well as how mental preparation influences sports skills applicable in different competitive situations.